The study of the overall management of PKNS Infra Berhad (PIB) from the year 2006-2008 / Nurull-Ain Salimi - Salimi, Nurull-Ain (2009)
This study is conducted as a partial fulfillment of the coursework of Project Paper (IBM 662). Title of the study is “The Study of the Overall Management of PKNS Infra Berhad (PIB) from the year 2006-2008”. The main objective of the study is to assess whether the interests and PKNS Selangor State government as a major equity holders maintained, to assess whether PKNS Infra Berhad (PIB) investment has generate profitable returns, and to evaluate whether PKNS Infra Berhad (PIB) management has properly managed and prudent in accordance with objectives set. This study was conducted under two types of data collection; Primary Data and Secondary Data. The Primary Data was collected discussion with staffs at National Audit Department and also with staffs of PKNS Infra Berhad (PIB), while the Secondary Data was collected from various sources such as internet, magazines, journals, book and articles. This case study will highlight certain recommendations which should be noted by PKNS Infra Berhad (PIB) for the future benefit.